Training in Cardiopulmonary Resuscitation and in-Hospital Cardiopulmonary Arrest Treated in A Second-Level Hospital in Spain - Ion Koldobika Iribar Diéguez; Jon Gil Barreiro; Irati Lanceta Barandiarán; Daniel Uzal Escudero; Aitziber Tranche Aristizabal; Ibai Mauduit Aznar; Irati Arístegi Sánchez; Itziar González Etxepare; María Gómez Martínez; Igor Garín Martín (Journal of Health Science and Reports, 2026)
Introduction: Cardiopulmonary arrest is a leading cause of premature death; it is unpredictable and potentially reversible. When it occurs in a hospital, the patient has a greater chance of survival. Bidasoa Hospital has a cardiopulmonary resuscitation training group and a structured response system for in-hospital cardiac arrest.Objective: To evaluate the training program and the epidemiological characteristics of in-hospital cardiorespiratory arrests treated since 2016.Method: Observational, retrospective and descriptive study. Registration records for CPR courses held between 2020 and 2025 were reviewed, analyzing the type of training received, participating professional categories, course repetition, and expressed satisfaction. In-hospital cardiac arrests recorded between January 2016 and December 2025, coded with diagnoses of cardiac arrest, were also analyzed. For each episode, sociodemographic and episode variables were collected following the international Utstein model. In the analysis of the results, p-values